Overview of anodization and silver coating for titanium alloys: Process parameters and biomedical insights - Andoko, Andoko; Khoyroh, Syafira Bilqis; Aminnudin, Aminnudin; Prasetya, Riduwan (Mechanical Engineering for Society and Industry, 2024)
Anodization is a critical electrochemical process for producing titanium oxide layers with varying characteristics, significantly influencing the physicochemical properties, biocompatibility, and performance of bone implants. This study systematically reviews the current state of research on the effects of anodization parameters and silver coatings on the morphology, functional groups, and phase identification of Ti-6Al-4V bone implants. By synthesizing findings from 18 relevant studies selected from 1044 screened articles (2000–2023), this review provides a comprehensive framework for understanding the role of anodization and silver coating in improving implant performance. The review highlights how variations in anodization parameters—such as electrolyte composition, voltage, and duration—significantly impact critical implant properties, including corrosion resistance, antimicrobial efficacy, and biocompatibility. Additionally, silver coatings are underscored for their antimicrobial benefits and ability to address challenges such as bacterial adhesion and biofilm formation. Beyond functional improvements, this review identifies gaps in the literature, such as the limited exploration of process optimization and the environmental implications of implant fabrication, offering actionable insights for future research. The novelty of this article lies in its holistic synthesis of fragmented findings, bridging material science, biomedical functionality, and sustainability. It provides a structured evaluation of key process parameters and their influence on implant performance, emphasizing the need for balanced approaches that integrate clinical effectiveness with environmentally responsible practices. By offering a unified perspective, this review serves as a valuable reference for advancing both research and practical applications in the development of high-performance bone implants.